'Breaking Barriers, Breaking Bread': Pilot study to evaluate acceptability of a school breakfast program utilising donated food. Issue 5 (24th October 2018) - Deavin, Natika; McMahon, Anne‐Therese; Walton, Karen; Charlton, Karen
Abstract : Aim: One in seven Australian schoolchildren do not consume breakfast. School‐based breakfast programs assist at‐risk children to meet their nutritional requirements and provide cognitive and behavioural benefits, but may result in significant food costs and waste. The present study aimed to explore acceptability and perceived benefits of a novel free primary school‐based breakfast program utilising donated food. Methods: Process evaluation included quantification of amount of food donated, number of meals provided and nutritional analysis of some of the meal items. Impact evaluation was based on thematic analysis of focus groups held with students, parents and teachers to explore their perspectives about the program. Breakfast diaries and hunger rating visual analogue scales were used to evaluate students' breakfast habits at home over five consecutive days. Results: The program saved 14.4 t of food from landfill through conversion into 44 000 meals. One‐fifth of children interviewed arrived at school without having breakfast at least once per week while one‐third of students reported being hungry on arrival at school. Benefits of participation in the program included increased willingness to attend school, improved alertness and behaviour, as well as creation of an equitable, supportive environment beneficial for low income or food insecure families. Conclusions: This novel breakfast program based on donated food was widely accepted by students, teachers and parents, providing benefits beyond the mere provision of food. It provides a model for school‐based interventions to combine breakfast programs with sustainable food production approaches.